PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM SOSIAL BANK INDONESIA DI DESA SUNGAI TOHOR KECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI - Yeni Marlina; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The criteria for the Bank Indonesia social program are community empowerment in areas that have superior commodities. One of them is sago, which is located in the Meranti island district, precisely in Sungai Tohor village. Empowerment activities have been well received by teh community. The purpose of this study is to determine community empowerment through Bank Indonesia social programs and to determine the supporting and inhibiting factors for community empowerment through the Bank Indonesia social program. This study uses the theory of Ambar Teguh (2004) in which empowernment is process. The stages of empowernment will be a benhmark. The results of this study indicate that: first, community empowerment through the Bank Indonesia social program in Sungai Tohor Village, Tebing Tinggi Timur District, has not been implemented optimally. Second, the supporting and inhibiting factors for community empowerment through Bank Indonesia's social programs, namely, the supporting factors for having a superior commodity in the form of sago and the support from the village government. The inhibiting factor is that the supporting technology in the village is still inadequate and there are personal conflicts between the Family Income Improvement Business groups (UP2K).                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                         Keywords: Empowerment, Program, Bank Indonesia